Youth Sport: A Frontier in Education - Littlefair, David; Nichol, David (Frontiers in Education, 2019)
Children are encouraged to participate in sport (Allender et al, 2006), through the school curriculum and specific dedicated clubs. Such provision can be described as a frontier in education with the role of the facilitator or ‘teacher’ usually being undertaken by a coach. However, the experiences of those in involved in this type of informal learning environment are not well researched or documented. Therefore, the aim of this study is to gain an insight into the experiences of children and stakeholder adults in such a setting. This study analyses and assesses the reality of the learning experience from the perspectives of the key stakeholders, children, coaches and parents through their involvement in a particular youth cricket club. A qualitative approach was deployed, in the form of three separate focus groups for parents (n=5), children (n=10) and coaches (n=3). At thematic analysis was conducted across the data set. The study highlighted a good development and learning environment within this particular youth cricket club and it alludes to a disparity within the wider field of youth sport. All three of the chosen groups, the players, parents and coaches, have aligned successfully to create a supportive, non-threatening environment, to allow the children to learn, develop their confidence, self-esteem and skill. In contrast, all groups highlighted the difference of their experiences of youth football, where a more negative experience was identified, potentially due to the subculture or the stakeholders involved.